Voiding urodynamics parameters for women with and without symptomatic pelvic organ prolapse - José Tadeu Carvalho Martins; Gisele Vissoci Marquini; Laura Aparecida Xavier de Abreu; Zsuzsanna Ilona Katalin de Jármy Di Bella; Marair Gracio Ferreira Sartori (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aims to characterize voiding urodynamics parameters suggestive of bladder outlet obstruction (BOO) diagnosis in women with and without symptomatic pelvic organ prolapse (POP). Methods: Cross-sectional research. Patients were selected and clinically evaluated with anamnesis, pelvic organ prolapse quantification system and standard Urodynamic Testing, performed according to International Continence Society and International Urogynecological Association guidelines (noninvasive uroflowmetry, followed by invasive cystometry and a Pressure/Flow Study). Included criteria: women aged 18 to 94 years with and without symptomatic POP and lower urinary tract symptoms . Exclusion criteria: patients who were not clinically feasible, undesirable, or impossible urodynamic test, or patients with urinary tract infection or neurological lower urinary tract dysfunction. Results: Voiding urodynamics parameters suggestive of BOO diagnosis found in women with POP were: maximum flow rate (Qmax) in the uroflowmetry ≤12mL/s; detrusor pressure at maximum flow (PdetQmax) >20cmH2O. When evaluating the differences between patients with and without POP, it was observed that those who presented some type of pPOP were mean age (y) older (67.6 × 58.9); had higher post-void residue volume (mL) (85.9 × 33.9); higher PdetQmax (cmH2O) values (41.3 × 28.5); lower Qmax (mL/s) values on uroflowmetry (8.5 × 20.4), lower maximum cystometric capacity (mL) (325.7 × 381.2), lower bladder compliance (mL/cmH2O) (39.8 × 46.1) and lower Qmax (mL/cmH2O) in the flow/pressure study (8.4 × 18.0) (p<0.001). Conclusion: The voiding urodynamics parameters listed in this study allows the evaluation of variables suggestive of BOO diagnosis in women with and without POP.